Simple Preparation of Components from Gardenia Jasminoides Ellis by Targeted Partition in Liquid Two-Phase Extraction - Liu, Sheng; Wei, Wanxing; Zhou, Min; Liu, Zhiping; Ling, Xiurong (Asian Journal of Chemistry, 2014)
Compounds were prepared from Gardenia jasminoides Ellis by targeted partition in two-liquid phase system without any chromatography columns. After Gardenia yellow and target guide reagent (polyethylene glycol, PEG) are dissolved in water, they would be partitioned with organic solvents in gradient to selectively give high-richened target component fractions. These fractions were crystallized, respectively to provide three components. Two of them were crocetin [b-D-glucopyranosyl-(1-6)-b-D-glucopyranosyl] ester (1) and crocin (2). Effects of partition on targeted compounds were investigated. The results not only shows that the component which is more oleophilic was most difficult to be extracted from the organic phase in these targeted partition systems, but also shows that using the target indicator PEG-2000, which is the lowest molecular weight in these systems, can facilitate selective separation of components.